2020
DOI: 10.1177/2158244020962816
|View full text |Cite
|
Sign up to set email alerts
|

BMI, Body Perception, and Approach to Eating and Diet in Adolescent Girls

Abstract: The aim of this study was to assess the effect of weight status on body perception and satisfaction, occurrence of Anorexia Readiness Syndrome (ARS), and dietary behaviors in adolescent girls. The study was conducted among 516 girls aged 14 to 16 living in Szczecin (Poland). The ARS Diagnosis Questionnaire designed by Ziółkowska and the author’s own questionnaire about self-perception of body were used, and anthropometric assessment was performed. The weight status significantly affected weight status percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Compensatory behaviors, especially when influenced by body size misperception [17], do not sustain healthy behaviors [29] and may lead to unwanted weight gain [42]. Promoting education about healthy body size perception is important for the cultivation of healthy behaviors in young women [63]. Frequent physical activity participation promotes increased body satisfaction [64], a healthier body image [23,24], and reduced risk of disordered eating [23].…”
Section: Discussionmentioning
confidence: 99%
“…Compensatory behaviors, especially when influenced by body size misperception [17], do not sustain healthy behaviors [29] and may lead to unwanted weight gain [42]. Promoting education about healthy body size perception is important for the cultivation of healthy behaviors in young women [63]. Frequent physical activity participation promotes increased body satisfaction [64], a healthier body image [23,24], and reduced risk of disordered eating [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ketidakpuasan terhadap bentuk tubuh dapat menurunkan kepercayaan diri dan depresi yang mengakibatkan seseorang melakukan pengaturan gaya hidup yang tidak sehat, seperti eating disorder dan excessive physical activities (Sonneville et al 2013). Remaja putri merupakan kelompok yang paling rentan untuk mengalami ketidakpuasan bentuk tubuh akibat adanya keinginan untuk mengikuti standar kecantikan yang ada (Sadowska et al 2020).…”
Section: Pendahuluanunclassified
“…Subjek pada kelompok status gizi lebih menyadari bahwa berat badannya agak atau sangat lebih dan beranggapan bahwa orang lain juga berpendapat hal yang sama. Sadowska et al (2020) menyatakan bahwa status gizi secara signifikan menunjukan persepsi terhadap penilaian ukuran tubuh, kepuasan terhadap bentuk tubuh, dan kebiasaan makan. Kualitas konsumsi makanan.…”
Section: Hasil Dan Pembahasanunclassified
“…Based on another previous study, it was found that 23.3% of high school students aged 13-16 years were involved in poor dietary practices 10 . Another study conducted by Joanna Sadowska, et all., 2020 showed that adolescents with a low body mass index often felt dissatisfied 11 .…”
Section: Introductionmentioning
confidence: 99%